Dehumanization and minimization of informal caregivers suffering: The legitimizing role of justice perceptions - Romão, Â.; Correia, I. (The Spanish Journal of Psychology, 2024)
Informal caregivers, who provide unpaid care work to individuals with disabilities, are devalued despite their important contributions to society. Identifying the factors contributing to their devaluation is crucial for recognizing and valuing their work. In two experimental studies, we examined (a) whether informal caregivers are dehumanized; (b) the moderating impact of belief in a just world (BJW) on this process; and (c) the predictive impact of BJW and the dehumanization of informal caregivers on the perception of informal caregivers’ suffering. In Study 1 (N = 180), a 2 (informal caregiver vs. non-caregiver) X 2 (female vs. male) between-participants design was used; in Study 2 (N = 205), there were two experimental conditions: female informal caregiver vs. male informal caregiver. Participants were randomly assigned to one description of a target and were asked to complete measures assessing the dehumanization of the target (Studies 1 and 2), the perception of the suffering of the target (Study 2), and a measure of BJW referring to themselves (Study 2). Results showed the expected dehumanization effect, such that participants attributed fewer uniquely human emotions to informal caregivers compared to non-caregivers, regardless of their gender (Studies 1 and 2). However, this effect was observed only among participants with higher BJW (Study 2). Furthermore, BJW and the dehumanization of informal caregivers predicted the minimization of the perception of informal caregivers’ suffering (Study 2). These results establish a theoretical relationship between these research areas and offer insights for practical implications and future research.